Três ensaios sobre as relações entre economia e Estado a partir de Keynes - Camara Neto, Alcino Ferreira (2010)
The first essay discusses if there is one conception of state and history in Keynes and in the Post Keynesian. The second essay discusses the origins of German Empire, its social, political and economical development and crisis. The third essays describes and analyses the hyperinflation happened in the twenties in Germany, including the different theoretical interpretations, specially The German School of Balance of Payments.